2013
DOI: 10.1002/masy.201300100
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and Differentiation of Adipose Stem Cells Towards Smooth Muscle Cells on Poly(trimethylene carbonate) Membranes

Abstract: Summary Multipotent human adipose stem cells (hASCs) are an abundant and potential source of cells for vascular tissue engineering when combined with a suitable biomaterial scaffold. Poly(trimethylene carbonate) (PTMC) has been shown to be a useful biodegradable material for tissue engineered vascular grafts due to its flexibility, excellent biocompatibility and enzymatic degradation by surface erosion in vivo. The purpose of the current study was to evaluate the proliferation and differentiation of hASCs towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 57 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…22 An interesting study showed that PTMC cross-linking affects the differentiation of adipose stem cells (ASCs) into smooth muscle cells (SMCs). 23 ASCs seeded on UV-crosslinked PTMC of low molecular weight (20 kDa) differentiated into SMCs more than those seeded on high molecular weight PTMC (250 kDa) cross-linked by gamma irradiation. Surface flexibility seems to influence cell attachment and differentiation (Young's moduli were 4.3 MPa and 6.6 MPa, respectively).…”
Section: Alteration Of Mechanical Propertiesmentioning
confidence: 92%
See 1 more Smart Citation
“…22 An interesting study showed that PTMC cross-linking affects the differentiation of adipose stem cells (ASCs) into smooth muscle cells (SMCs). 23 ASCs seeded on UV-crosslinked PTMC of low molecular weight (20 kDa) differentiated into SMCs more than those seeded on high molecular weight PTMC (250 kDa) cross-linked by gamma irradiation. Surface flexibility seems to influence cell attachment and differentiation (Young's moduli were 4.3 MPa and 6.6 MPa, respectively).…”
Section: Alteration Of Mechanical Propertiesmentioning
confidence: 92%
“…UV reactive groups are then easily introduced by esterification with (meth)acryloyl chloride (or anhydride) as the most common approach. 23,38,39 Cinnamoyl chloride is also employed as an alternative UV reactive moiety. [40][41][42] The radical addition reaction of the double bonds can be performed by UV irradiation, and photosensitizers such as benzophenone are sometimes added to prompt the reaction.…”
Section: Cross-linkingmentioning
confidence: 99%